Shantala: vivências na gestação, parto e puerpério - Cavalheiro, Andriele dos Santos (2024)
Shantala is a massage technique indicated for babies, aiming to assist in parenting by building the bond with those who practice it, especially the mother. Associating Shantala with care practices can be seen as a complementary form of humanized post-birth care and can help reduce parental stress. The objective of this study was to understand the level of knowledge of pregnant women about the Shantala technique and, after learning it, to evaluate its applicability to the baby during the puerperium. This is a multi-case research of a descriptive nature with a qualitative approach. The research took place in three stages: the first was a semi-structured interview to get to know the participants and identify their knowledge about Shantala. In the second stage, four Shantala workshops were held in two Basic Units, in a Family Health Strategy and one in the home of one of the participants in Santa Maria-RS. In the third stage, the second semi-structured interview took place, already with babies with 1 month of life, the participants answered interview II in relation to the applicability of Shantala after the workshop and their experiences of the puerperium. Data analysis was performed by content analysis, following three phases: 1) pre-analysis;2) exploration of the material 3) treatment of the results, inference and interpretation. Six women followed up by the Santa Maria primary health care took part in this study. The statements were categorized by interview I and II, in the categorization of interview I, three subcategories were obtained: I - Pregnant women's previous knowledge about Integrative and Complementary Health Practices and Shantala; II - Previous experiences of pregnant women regarding common symptoms that babies present; III - Pregnant women's knowledge about home methods to treat symptoms in babies. In the categorization of interview II, four subcategories were obtained: I - Reports on the experience of childbirth; II – Postpartum experience reports; III use of home methods during the puerperium; IV – Application of Shantala in the first months of the baby's life. In the participants' statements, the issue of massage to relieve colic, crying, and to help the baby relax and sleep was identified. They recognized some home methods to relieve symptoms that babies usually present, the most frequent in the speeches was the use of teas. Some of the participants also shared experiences during childbirth, such as obstetric violence and their experiences in the postpartum period where they reported that the greatest difficulty they encountered when performing the massage was due to the lack of time organization, in addition to other difficulties required such as taking care of the house and other children. The research exposed the participants' lack of knowledge in relation to the PICS and Shantala in interview I, the workshops were indispensable for the knowledge about Shantala. Interview II showed acceptance of Shantala by the participants, who performed the practice on babies, mainly as an immediate resource, to relieve colic, constipation and sleep. They also made reports about childbirth and the puerperium and, exposing their daily situations, allowed them to better understand the importance of the massage in the day-to-day life of women and their families.